Uveitis associated with juvenile arthritis: a continued cohort study 40 years after uveitis onset - Angelika Skarin; Elisabet Berthold; Ola Rauer; Elisabeth Bengtsson-Stigmar (BMC, 2022)
Abstract Background A third follow-up study, mean 40.7 years after uveitis onset, of a cohort originally consisting of 55 Swedish patients with uveitis associated with juvenile arthritis. Method A retrospective study of the patients' ophthalmic medical records. The results were compared to those of the same cohort previously studied at mean 7.2 and 24.0 years after uveitis onset. In the present follow-up study, 30 of the original 55 patients consented to participate. Of these, 26 had ophthalmic medical records that were reviewed. Results In the 30 participants, active uveitis was seen in 43.4%, cataracts in 66.6% and glaucoma in 40.0%. When comparing data from previous follow-ups of the same cohort, a total of 61.8% were reported to have had cataracts at any of the three follow-ups, 29.0% had glaucoma or ocular hypertension and 12.7% had severe visual impairment in both eyes. At mean 40.7 years after uveitis onset 20% of patients in the original uveitis cohort were deceased. In 4 of the 11 deceased individuals, rheumatic disease was stated as the main cause of death, and in 3 it was considered a contributory factor in the patients deaths. Conclusions Uveitis associated with juvenile arthritis can be active into midlife and possibly longer. Ocular complications and visual loss increased up to 40 years after uveitis diagnosis. The mortality rate of this cohort was higher than that of a corresponding Swedish population. Lifelong ophthalmic check-ups are probably necessary for patients diagnosed with this type of uveitis.